GAMBARAN STATUS PEMBERIAN ASI EKSKLUSIF DAN STATUS GIZI BALITA UMUR 6-24 BULAN - Apriyanto Anu; Salman Salman; Liean A. Ntau; Sofyawati D. Talibo (JOURNAL HEALTH AND NUTRITIONS, 2022)
Exclusive breastfeeding can be defined as a practice whereby the infants only receive breast milk without complementary foods for the first six months. Early initiation of breastfeeding is beneficial for both mother and child. The prevalence of malnutrition status in toddlers aged 6 to 24 months is 17.75% undernourished toddlers are 32.47% severely stunted toddlers are 25,49% stunted toddlers are 25,08% severely underweight toddlers are 11,98% and underweight toddlers are 22,45%. The study aims at finding out the overview of exclusive breastfeeding status and toddlers aged 6 to 24 months nutritional status in Pauwo Village, Kabila Subdisrict, Bone Bolango District. It applies descriptive survey research with the numbers of samples are seven toddlers. The research variale are the independent variable namely the overview of exclusive breastfeeding status and toddlers aged 6 to 24 months nutritional status in Pauwo Village, Kabila Subditrtict, Bone Bolango District. Finding reveals that toddles who receive exculsive breastfeeding are 19 toddlers (76%) and non-exclusive breastfeeding status are six toddlers (24%). In addition, the toddlers’s nutritional status with overnutrition category is as many as one toddler (4$), normal nutrition is as many as 20 toddlers (80%), undernutrition is as many as two toddlers (8%) and malnutrition is as many as two toddlers (8%). In short, most toddlers in Pauwo Viillage, Kabila Subdisctrict, Bone Bolango District, receive exclusive breastfeeding and have normal nutritional status.Pemberian ASI eksklusif merupakan pemberian ASI saja kepada bayi tanpa diberi makanan dan minuman lain sejak dari lahir sampai 6 bulan. Menyusui sejak dini mempunyai dampak yang positif baik bagi ibu maupun bayinya. . Prevalensi status gizi buruk pada balita usia 6-24 sebesar 17,57% , balita gizi kurang 32,47%, balita sangat pendek 25,49%, balita pendek 25,08%, balita sangat kurus 11,98% sedangkan balita kurus 22,45%. (Riskesdas, 2018). Penetian ini bertujuan untuk mengetahui gambaran status gizi pemberian ASI eksklusif dan status gizi balita umur 6-24 bulan di Kelurahan pauwo Kecamatan Kabila Kabupaten Bone Bolango. Jenis penelitian ini adalah  penelitian  survey deskriptif. Jumlah sampel sebanyak 7 sampel. Vareabel penelitian yaitu variabel variabel mandiri yaitu gambaran status pemberian ASI eksklusif dan status gizi balita usia 6-24 bulan  di Desa Pauwo  Kabupaten Bone Bolango. Hasil penelitian ini menunjukkan bahwa balita yang mendapatkan ASI eksklusif berjumlah 19 orang (76%) dan yang tidak Eksklusif sebanyak 6 orang (24%). Status gizi anak balita dengan kategori gizi lebih 1 orang (4%), gizi baik 20 oramg (80%), gizi kurang 2 orang (8%) dan gizi buruk sebanyak 2 orang (8%). Kesimpulan dalam penelitian ini yaitu sebagian besar balita di Kelurahan Pauwo Kecamatan Kabila Kabupaten Bone Bolango medapatkan ASI eksklusif dan berstatus gizi baik.